Evaluation of cyclic oxidation behavior and mechanical properties of nanocrystalline composite HVOF coatings on SA 210 grade C material. (March 2019) - Premkumar, K.; Balasubramanian, K.R.
Abstract: The cyclic oxidation behavior of high velocity oxygen fuel (HVOF) sprayed nanocrystalline and conventional (27% Cr3 C2 –23% Ni-50% Cr) powder coatings on SA 210 Grade C boiler material was investigated in air at 900 °C for 50 cycles. The kinetics of oxidation has been developed with the help of weight change measurements for both the nanocrystalline and conventional coated specimens, and the results were compared with the bare boiler material. The coatings were characterized relative to coating thickness, porosity, microhardness, and microstructure. The oxidation products of the nanocrystalline, conventional coated, as well as bare boiler material, were analyzed using X-ray diffraction (XRD), elemental mapping techniques and scanning electron microscopy/ energy dispersive spectroscopic analysis (SEM/EDS). The characterization of the feedstock powder was performed using high resolution transmission electron microscope (HRTEM). The bare boiler material suffered during oxidation in the form of intense spalling and peeling of oxide scale from the surface, which may be due to the formation of unprotective oxide scale, Fe2 O3 . From the results, it was identified that both conventional and nanocrystalline coatings have better oxidation resistance compared to the bare material. However, the nanocrystalline coating was found to be more protective against oxidation. The grain boundary diffusion was improved in the nanocrystalline coating which promotes the creation of a denser scale of Cr2 O3 with a higher rate, and also it helps to mitigate the Cr depletion at the metal/scale interface. The nanocrystalline coating was found to be superior to the conventional coating and reduced the weight gain of SA 210 Gr C steel by 98.76%. The protective Cr2 O3 phase formed on the oxide scale was found to impart a better oxidation resistance. The low percentage of porosity in the nanocrystalline coating was observed to be favorable for anti-corrosion properties. Highlights: Cyclic oxidation behaviour of HVOF coated SA 210 Gr C steel was investigated at 900 °C in air. Conventional and Nanocrystalline composite coatings were found to exhibit oxidation resistance during cyclic conditions. The Nanocrystalline coating was found to be superior to conventional coating and the reduced weight gain is 98.76%. The protective Cr2 O3 phase formed in the oxide scale might have imparted the better oxidation resistance to the coating surface.